Comparison of the Dual Therapy of Ilaprazole-Amoxicillin and the Bismuth Quadruple Therapy of Ilaprazole-Amoxicillin-Furazolidone-Bismuth Glycyrrhizinate for Eradication of Helicobacter pylori - Min Niu; Yan Zhou; Yan Zhou; Yunqian Xie; Xue Li; Yonggang Tian; Li Yao; Ximei Li; Ximei Li; Hengjun Gao; Hengjun Gao; Feihu Bai; et al. (Frontiers Media S.A., 2022)
Objective: The present study aims to compare the safety and efficacy of an amoxicillin/ilaprazole regimen with a bismuth quadruple regimen as the first-line treatment for eradicating Helicobacter pylori (H. pylori) infection.Methods: This was an open-label, randomized, single-center study involving 450 patients with untreated H. pylori infection who were randomly assigned to an Ilaprazole-amoxicillin-furazolidone-bismuth glycyrrhizinate (IAFB) quadruple therapy group for 14 days, a bismuth quadruple therapy group for 10 days, or Ilaprazole-amoxicillin (IA) dual therapy group for 14 days. The 13C urea breath test determined that H. pylori had been eliminated 4-6 weeks after treatment. For patients who failed the first treatment, mucosal tissues (two gastric antrum and one gastric body) were taken under gastroscope for the culture of H. pylori, drug sensitivity, the CYP2C19 gene, and globular degeneration.Results: In the intention-to-treat analysis, the eradication rates of H. pylori in the IAFB-14-day group, the IAFB-10-day group, and the IA-14-day group were 84.0, 79.3, and 88.0%, respectively. In the per-protocol analysis, the eradication rates in the three groups were 94.7, 87.5, and 93.0%, respectively. The resistance rates of patients who failed H. pylori eradication were 68.9% (22/32) for amoxicillin, 90.6% (29/32) for clarithromycin, 68.9% (22/32) for metronidazole, and 87.5% (28/32) for levofloxacin, and the extensive metabolizers of CYP2C19 polymorphism were 59.3% (19/32), the intermediate metabolizers were 34.4% (11/32), and the poor metabolizers were 6.3% (2/32).Conclusion: For newly treated patients with H. pylori infection in China, the efficacy of IA therapy for 14 days was similar to IAFB quadruple therapy for 10 or 14 days with better compliance and less cost. Therefore, these therapies can be considered first-line regimens for empirical treatment.Clinical Trial Registration: [http://www.chictr.org.cn/searchproj.aspx], identifier [ChiCTR2100052308].